ESTADO E CULTURA NA CONTEMPORANEIDADE: Portugal e Brasil em foco - Maria Manuel Baptista (Universidade Federal do Maranhão, 2007)
Outline of analytical elements about the Contemporaneous State according to its insertion in a money-oriented civilization where the focus goes to the study of the relation State/Culture, having as empirical reference the European scenario, highlighting Portugal and the Brazilian setting. The discussions have as a leading thread the contradictions in the fabric of the State, aiming at superseding traditional interpretations that are founded on dichotomies. The Contemporaneous State is analyzed at the point where processes of democratization and adjustment to the world order of the capital under a globalization trend meet, exploring a thesis that contrasts aspects between State/Civil Society seen within the dynamics of public policies. It highlights the proposition issued by the cultural democracy as a challenge of our times.